Peri-Procedural Platelet Reactivity in Percutaneous Coronary Intervention - Alexopoulos, Dimitrios; Xenogiannis, Iosif; Vlachakis, Panagiotis; Tantry, Udaya; Gurbel, Paul A. (Thrombosis and Haemostasis, 2018)
Platelet activation and aggregation play a pivotal role in thrombotic complications occurring during percutaneous coronary intervention (PCI), and peri-PCI anti-platelet therapy represents a standard of care. High platelet reactivity prior to PCI has been correlated with an increased incidence of peri-procedural myonecrosis. Pre-PCI platelet reactivity predicts post-PCI platelet reactivity and has a prognostic impact on subsequent ischaemic and bleeding events, so as the platelet inhibition measured post-PCI. Many anti-platelet treatment strategies, including aspirin, glycoprotein IIb/IIIa inhibitors, P2Y12 receptor blockers and vorapaxar, are being used in the routine clinical practice to modify platelet reactivity at each stage, e.g. pre-, during and post-PCI. Anti-platelet strategies with a ‘stronger and faster’ pharmacodynamic effect than clopidogrel have been mostly adopted in patients with acute coronary syndromes. However, several issues regarding the anti-platelet treatment such as benefits/risks of anti-platelet therapy pre-treatment and duration, and definite association between speed and potency of various anti-platelet agents and clinical outcomes remain controversial. We believe that a better understanding of peri-PCI platelet reactivity and its relations to outcomes may lead to the development of more effective and safe treatment strategies.
Keywords: coronary angioplasty; anti-platelet treatment; platelet reactivity